Saccade Latency and Fixation Stability: Repeatability and Reliability - Gro Horgen; Trine Langaas (Journal of Eye Movement Research)
This study aimed to investigate the repeatability and reliability of saccadic latency and fixation stability as a function of sighting-dominance and contact lens wear. Eye movements were recorded in 12 healthy adults who performed a pro- saccade and a fixation task in four conditions; baseline, retest, non-sighting eye viewing and plano contact lens wear. The re-sults showed that saccadic latency and fixation stability (indexed via logBCEA) have good internal consistency, reliability and repeatability, which are not influenced by sighting- dominance or contact lens wear. For standard deviation of eye position, internal consistency was low to moderate. The results also indicated that the non-sighting eye is slightly less stable than the sighting eye and that wearing a contact lens decreases precision.